Histopathological Features of Lucio’s Phenomenon in Leprosy Patients: A Retrospective Study - Khoirunnisa; Nurrachmat Mulianto; Novan Adi Setyawan; Alamanda Murasmita (Faculty of Medicine, Universitas Airlangga, 2026)
Background: Mycobacterium leprae causes leprosy, as a chronic infectious disease that is still a major public health concern in endemic nations like Indonesia. Lucio’s phenomenon (LP), which is marked by necrotizing vasculitis and ulcerative skin lesions, is an uncommon but severe reactional state that is typically linked to untreated or insufficiently treated diffuse lepromatous leprosy. Histopathological examination is essential for diagnostic confirmation. Purpose: This study aimed to describe the histopathological features of Lucio’s phenomenon in leprosy patients treated at Dr. Moewardi General Hospital, Surakarta. Methods: A retrospective study was conducted using medical records and histopathological slides of patients diagnosed with the Lucio’s phenomenon at the Dermatology and Venereology Clinic, Dr. Moewardi Hospital, from January 2018 to June 2024. Demographic data (age, sex) and histopathological findings were analyzed. Result: Fifteen cases of the Lucio’s phenomenon were identified, consisting of 10 males (67%) and 5 females (33%). Most patients (67%) were younger than 50 years. Histopathological analysis showed endothelial colonization by acid-fast bacilli in all patients (100%). Additional features included leukocytoclastic vasculitis in 12 patients (75%), epidermal necrosis in 9 patients (60%), and fibrinoid necrosis in 6 patients (40%). Conclusion: Lucio’s phenomenon remains a rare but life-threatening manifestation of lepromatous leprosy. Histopathological examination reveals consistent features such as endothelial bacillary colonization and necrotizing vasculitis, which are crucial for establishing the diagnosis. Increased awareness and recognition of these features are essential to ensure early diagnosis and appropriate management, thereby reducing morbidity and mortality associated with this condition.